Ciclo reproductivo de Lactophrys quadricornis (Pisces: Ostraciidae) de la costa nororiental de Venezuela - Ruiz, Lilia J (1999)
Reproductive biology was studied in Lactophrys quadricomis, from samples collectéd monthly from May 1990 to Apri11991 in the east coast of Venezuela. Sex ratio was 1: 1; half the population matured at total lenght of 198 mm for males and 222 mm for females. Minimal sizes for maturity was 160 and 170 mm of L.T in males and females, respectively. The Gonadosomatic Index (IG) and gonadal maturity stages sugest year around reproduction with two peaks: from lune through September, and from January through February. Weight, ovary lenght and frequency of females in stages IV and V, are the evidence. Asynchronous development of the ovocytes with diameters .between 0.399 to 0.930 mm, indicates that spawning is fractionate. Mean fecundity was 112 536 ± 57 047 .97 eggs, and increases with lenght and weight of the fish and weight and length of the ovarie